ESTIMATION OF AGE FROM COUNTING OF CONCENTRIC LAMELLAE PER OSTEON IN HUMAN COMPACT BONE (Indian Internet Journal of Forensic Medicine and Toxicology, 2005)
A histological study was conducted on 100 subjects of both sexes (M-50, F-50) from the compact portion of the tibia to observe  changes related to age in the lamellae per osteon, in the haversion system in human compact bone. In majority of cases it was  observed that the number of lamellae was found to be 6 to 10 per osteon from 18 to 55 yrs. of age. After 55 yrs. of age, 3 to 4 lamellae were seen, per osteon.
Keywords: Compact bone; Lamellae per Osteon; Age Determination